La emergencia... en el corazón del constitucionalismo peruano: paradojas, aporías y normalización - Siles Vallejos, Abraham (2015)
States of emergency haven’t been unconnected to Peruvian history. When the first Constitution was proclaimed, a regime of suspension of constitutional order was declared.  Today,  the normalization of this reality continues being firmly present in the institutional life of the country.In this paper, the author analyzes the paradox that this notion entrails. With this purpose, he goes back to the evolution that this concept has suffered in doctrine. Also, he presents an historical approach to the presence of the institution in our country.